Elastic and structural properties of V₂O₅-PbO-ZnO and V₂O₅-TeO₂-Li₂O glass systems / Siti Laila Abdul Hamid - Abdul Hamid, Siti Laila (2015)
Ternary (55₋ₓ)V₂O₅₋45PbO-(ₓ)ZnO (ₓ= 0-15 mol%) and 35V₂O₅₋(65₋ₓ)TeO2-(ₓ)Li₂O (ₓ = 10-50 mol%) glass series were prepared by the melt-quenching method. Elastic and structural properties of the glasses were investigated by measuring sound velocity using the pulse-echo-overlap technique and Fourier Transform Infrared (FTIR) spectroscopy, respectively. Properties such as density (p), molar volume (Vₐ), and glass transition temperature (Tg) were also reported. For (55-ₓ)V₂O₅₋45PbO- (ₓ)ZnO glass series, results from the study showed that both longitudinal and shear velocities decreased at x = 5 mol% with the increase of ZnO concentration. The independent longitudinal and shear moduli, CL and ju and Young's modulus (Y) also showed decreasing trend at ₓ = 5 mol% as the fraction of ZnO increases. FTIR analysis showed an increase in non-bridging oxygen (NBO) as indicated by the increase in intensity of VO4 assigned peaks at ₓ = 5 mol% while the increase in intensity of VO5 assigned peaks at ₓ > 5 mol% indicates increasing bridging oxygen (BO). The glass transition temperature (Tg) showed a decrease at x = 0-5 mol% which implies increase in non-bridging oxygen (NBO) while an increase of Tg for ₓ = 10-15 mol% indicates the decrease in NBO.